Feasibility Investigation of Geothermal Energy Heating System in Mining Area: Application of Mine Cooling and Aquifer Thermal Energy Exploitation Technique - Luwei Ding; Zetian Zhang; Baiyi Li; Shengming Qi; Hengfeng Liu; Shuo Liu (Energies, 2024)
Mine heat hazards have resulted in large amounts of high-quality coal resources in deep that cannot be mined. The mining industry is paying more and more attention to the extraction and utilization of geothermal energy in mines, while at the same time reducing the underground temperature to realize co-extraction of coal and heat. In addition, coal mines tend to burn large amounts of coal to heat mine buildings and provide hot water for workers’ daily baths, creating operating costs and increasing greenhouse gas emissions. Therefore, it is of great significance to investigate the feasibility of extracting geothermal energy to provide the daily heat load for mines. Currently, there is little research on the feasibility of geothermal energy extraction and utilization in productive mines instead of abandoned mines. In this study, according to the actual situation of Xinhu mine in eastern China, a combined geothermal water system and heat-pump heating system is proposed, aiming to effectively realize mine cooling and geothermal exploitation and utilization. The geothermal storage capacity in the area is analyzed, and an economic analysis is developed. The economic analysis indicates that the main factors affecting the feasibility of the system are the number of mine users, the distance from the geothermal production well to the mine buildings, and the coal price. The research shows that the economic efficiency of the system is better when the heating scale is larger and the distance is smaller. As coal prices rise, the combined geothermal water and heat-pump heating system will be more economical than traditional coal heating. If a mine has 2000 workers, the application of this system can prevent 334.584 t of CO2 emissions per year.